A novel approach for preparation of the antisera reagent for potency determination of inactivated H7N9 influenza vaccines. Issue 2 (29th January 2016) - Schmeisser, Falko; Jing, Xianghong; Joshi, Manju; Vasudevan, Anupama; Soto, Jackeline; Li, Xing; Choudhary, Anil; Baichoo, Noel; Resnick, Josephine; Ye, Zhiping; McCormick, William; Weir, Jerry P.
Abstract : Background: The potency of inactivated influenza vaccines is determined using a single‐radial immunodiffusion (SRID) assay and requires standardized reagents consisting of a Reference Antigen and an influenza strain‐specific antiserum. Timely availability of reagents is a critical step in influenza vaccine production, and the need for backup approaches for reagent preparation is an important component of pandemic preparedness. Objectives: When novel H7N9 viruses emerged in China in 2013, candidate inactivated H7N9 influenza vaccines were developed for evaluation in clinical trials, and reagents were needed to measure vaccine potency. Methods: We previously described an alternative approach for generating strain‐specific potency antisera, utilizing modified vaccinia virus Ankara vectors to produce influenza hemagglutinin (HA)‐containing virus‐like particles (VLPs) for immunization. Vector‐produced HA antigen is not dependent upon the success of the traditional bromelain‐digestion and HA purification. Results: Antiserum for H7N9 vaccines, produced after immunization of sheep with preparations of bromelain‐HA (br‐HA), was not optimal for the SRID assay, and the supply of antiserum was limited. However, antiserum obtained from sheep boosted with VLPs containing H7 HA greatly improved the ring quality in the SRID assay. Importantly, this antiserum worked well with both egg‐ and cell‐derived antigen and was distributed to vaccine manufacturers. Conclusions: Utilizing a previously developed approach for preparing vaccine potency antiserum, we have addressed a major bottleneck encountered in preparation of H7N9 vaccine reagents. The combination of br‐HA and mammalian VLPs for sequential immunization represents the first use of an alternative approach for producing an influenza vaccine potency antiserum.